Exploring the metabolic and flavoromic variations of germinated sunflower seed during roasting conditions - Shuangshuang Guo; Weijie Lan; Xiao Chen; Yan Ge (Food Materials Research)
The metabolite and flavor characteristics of roasted germinated sunflower seeds (RGSF) were evaluated and compared with those of roasted ungerminated sunflower seeds (RUSF) by gas chromatograph-flame ionization detector (GC-FID) and headspace solid phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS). During roasting, α-tocopherol, β-sitosterol, fructose, and glucose content were higher at 125 °C compared to those at 135 and 145 °C in RGSF, and lower reductions of alanine, glycine, phenylalanine, serine, asparagine, and γ-aminobutyric acid (GABA) content at 125 °C in RGSF. Considering their nutritional value, it is suggested that sunflower seeds are roasted at 125 °C. The dominant volatile compounds in RGSF were α-pinene, furfural, pyrazines, 1-octen-3-ol, and 2-methylbutanal. High-temperature heating for long term led to a large accumulation of unpleasant odors like pyridine, hexanal and nonanal, especially in RUSF. To examine the distribution of the individual metabolites and flavor compounds among different roasting conditions. A heatmap diagram combined with agglomerative hierarchical clustering (AHC) analysis and principal component analysis (PCA) showed that most Maillard reaction substitutes (amino acids and reducing sugars), products (2-methylpyrazine 2-ethyl-3,5-dimethyl-pyrazine, and 3-ethyl-2,5-dimethylpyrazine), and Strecker degradation products (3-methylbutanal, 2-methylbutanal, and isobutanal) contributed to separate RGSF from RUSF.